2007
DOI: 10.1111/j.1471-4159.2007.04614.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma cholesterol does not affect brain Aβ in mice lacking the low‐density lipoprotein receptor

Abstract: Epidemiological studies support an association between vascular risk factors, including hypercholesterolemia, and Alzheimer's disease (AD). Recently, there has been much interest in the possibility that hypercholesterolemia might directly promote b-amyloid (Ab) production. Indeed, in vitro studies have shown that increasing cellular cholesterol levels enhances Ab production. However, studies in AD transgenic mouse models have not consistently found that elevated plasma cholesterol leads to increased Ab product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 60 publications
(83 reference statements)
3
31
2
Order By: Relevance
“…Indeed while longer term exposure to elevated serum cholesterol may eventually impact behavior, the 16-week exposure studied here seems to have had few if any behavioral effects. This lack of effect is, however, consistent with our recent findings that dramatically elevated plasma cholesterol levels in LDLR-/-mice, whether induced by high cholesterol, high fat, or high fat/high cholesterol diets, do not substantially alter brain cholesterol levels nor affect levels of brain Aβ 40 or 42 [11].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Indeed while longer term exposure to elevated serum cholesterol may eventually impact behavior, the 16-week exposure studied here seems to have had few if any behavioral effects. This lack of effect is, however, consistent with our recent findings that dramatically elevated plasma cholesterol levels in LDLR-/-mice, whether induced by high cholesterol, high fat, or high fat/high cholesterol diets, do not substantially alter brain cholesterol levels nor affect levels of brain Aβ 40 or 42 [11].…”
Section: Discussionsupporting
confidence: 92%
“…LDLR itself is expressed in the brain, and while it has generally been considered to be less important functionally in the nervous system [13] than other LDLR family members, several recent studies have suggested that LDLR may affect brain function [11,12,19,23]. We therefore undertook a detailed behavioral analysis of LDLR-/-mice and in addition given the interest in serum cholesterol as a possible risk factor for the cognitive dysfunction seen in AD [3,5,28], we used the fact that serum cholesterol levels can be modulated by diet in LDLR-/-mice [31] to examine the effects of systemic hypercholesterolemia on behavioral function as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in PDAPP mice crossed to LDLR Ϫ/Ϫ mice there was no significant change in human A␤ levels, although there was a trend toward increased A␤ deposition in mice lacking LDLR (36). A different group looking at the effect of LDLR deletion on mouse A␤ levels found no changes in comparison to WT mice (49). Our studies have found that LDLR overexpression in the mouse brain dramatically decreased A␤ deposition in APP/PS1 transgenic mice.…”
Section: Figure 8 Direct Interaction Between A␤ and Ldlrcontrasting
confidence: 47%
“…In mouse studies, modulation of LDLR protein levels in the brain altered apoE amounts. LDLR Ϫ/Ϫ mice had significantly elevated amounts of apoE in the brain and cerebrospinal fluid (36,37,49,50), whereas mice overexpressing LDLR in the brain had lower levels of apoE (27). In the current study, we demonstrate that modulation of LDLR levels in astrocytes similarly alters apoE levels.…”
Section: Figure 8 Direct Interaction Between A␤ and Ldlrmentioning
confidence: 99%